Acute intermittent porphyria: identification and expression of exonic mutations in the hydroxymethylbilane synthase gene. An initiation codon missense mutation in the housekeeping transcript causes "variant acute intermittent porphyria" with normal expression of the erythroid-specific enzyme. - Chen, C H; Astrin, K H; Lee, G; Anderson, K E; Desnick, R J (The Journal of Clinical Investigation, 1994)
Acute intermittent porphyria (AIP), an autosomal dominant inborn error, results from the half-normal activity of the heme biosynthetic enzyme, hydroxymethylbilane synthase (EC 4.3.1.8). Diagnosis of AIP heterozygotes is essential to prevent acute, life-threatening neurologic attacks by avoiding various precipitating factors. Since biochemical diagnosis is problematic, the identification of hydroxymethylbilane synthase mutations has facilitated the detection of AIP heterozygotes. Molecular analyses of unrelated AIP patients revealed six exonic mutations: an initiating methionine to isoleucine substitution (M1I) in a patient with variant AIP, which precluded translation of the housekeeping, but not the erythroid-specific isozyme; four missense mutations in classical AIP patients, V93F, R116W, R201W, C247F; and a nonsense mutation W283X in a classical AIP patient, which truncated the housekeeping and erythroid-specific isozymes. Each mutation was confirmed in genomic DNA from family members. The W283X lesion was found in another unrelated AIP family. Expression of each mutation in Escherichia coli revealed that R201W, C247F, and W283X had residual activity. In vitro transcription/translation studies indicated that the M1I allele produced only the erythroid-specific enzyme, while the other mutant alleles encoded both isozymes. These mutations provide insight into the molecular pathology of classic and variant AIP and facilitate molecular diagnosis in AIP families. Images